Pemberian Bantuan Langsung dan Edukasi Pencegahan Penularan Covid-19 di Pusat Pengembangan Anak GMII Betfage Sorong - Rumalutur, Sonny; Harling, Vina N. Van; Martono, Stefany Margareta (Jurnal Karya Abdi Masyarakat, 2021)
The government policy given some time ago in the form of physical distancing caused the number of household economies to decline with reduced sources of income, especially for households in the suburbs of Yohan in the city of Sorong, where the majority of the population living in the area made their living as street vendors and the farmer. The purpose of this service program is to provide basic food assistance and provide education about the prevention of covid-19 transmission for children at the GMII Betfage Child Development Center. The service program will be carried out on 12 and 13 February 2021 with the method of conducting surveys, preparation of educational materials, technical preparation of service activities, implementation of activities, and evaluation. This community service activity program was welcomed by parents, partners, and also children who were in the GMII Betfage Child Development Center. So it can be said that the expected output, namely the need for necessities of children, can be met and can be used wisely to alleviate the impact of Covid-19 that has occurred when it has been achieved